POM / MXene porous membrane-based electrode material and preparation method and application thereof
By growing POM in situ between MXene layers and coated with DODA, POM/MXene-based porous structures with high porosity and large specific surface area were prepared, which solved the problems of poor POMs stability and easy MXene stacking, improving the performance of supercapacitor electrode materials and simplifying the preparation process.
Patent Information
- Application Number
- CN202510074536.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, POMs have poor stability and high solubility, MXene materials are easy to stack, and the porous membrane structure made of traditional porous structure preparation methods is low in porous membrane structure, and the preparation process is complex, high cost and great environmental harm.
By growing POM in situ between MXene layers, increasing the layer spacing and preventing POM dissolution, then coating POM/MXene using the surfactant DODA, POM/MXene matrix composites were prepared and cast on the conductive substrate through a self-assembly process to form a rime-like porous structure.
A porous structure with high porosity and large specific surface area is realized, which improves the specific capacitance and cyclic stability of the electrode material, simplifies the preparation process, reduces costs, and reduces the harm to the environment.
Smart Images

Figure HDA0005246667440000011 
Figure HDA0005246667440000012 
Figure HDA0005246667440000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitor electrode materials, and in particular to an electrode material based on a POM / MXene porous film, and a preparation method and application thereof. Background Art
[0002] In the face of the rapid growth of global energy demand, high-performance energy storage devices are important for efficient use of energy. Supercapacitors have great potential in the field of portable electronics and microelectronics due to their excellent power density and long service life. According to the energy storage mechanism, supercapacitors are divided into two categories. One is the double-layer supercapacitor and the other is the Faraday pseudocapacitor supercapacitor. The total energy storage in pseudocapacitor supercapacitors is much larger than that in double-layer supercapacitors; however, the latter exhibits better electrochemical stability. Therefore, it is of great significance to use different materials for the same electrode preparation to obtain synergistic effects. Polyoxometalates (POMs) are materials with pseudocapacitive properties and have transition metal anion clusters. They have attracted great interest due to their unique redox properties and multi-electron transfer capabilities. However, POMs have poor stability and high solubility in aqueous electrolytes, which limits their effective use. Researchers usually use coating and doping methods to prevent their dissolution to maximize their advantages in many applications. MXene is a promising material for the production of MXenes due to its desirable properties, such as metal-like electronic conductivity (over 10,000 S cm -1 ), solution processability and high volumetric capacitance (up to 1500F·cm -3 ), is considered to be a promising double-layer capacitor electrode material. However, its interlayers are easily stacked, resulting in poor electrochemical performance. Constructing a three-dimensional structure and inserting substances between layers are effective ways to solve its restacking. So far, researchers have developed various methods for preparing three-dimensional structures, especially porous structures, such as 3D printing, template method, breathing pattern method, etc. The traditional method for preparing three-dimensional porous structures produces porous membranes with a single structure, relatively low porosity and specific surface area. These will limit the further improvement of its performance and its application in a wider field. Therefore, if a novel three-dimensional porous structure with high porosity and large specific surface area can be obtained, and its convenient construction can be achieved, then this will have a great driving effect on the improvement of the performance of electrode materials and their practical applications. Summary of the invention
[0003] The object of the present invention is to provide a POM / MXene porous membrane-based electrode material loaded on a conductive substrate and a preparation method thereof that can be applied to supercapacitor electrodes, so as to solve the problems in the prior art of high solubility and poor stability of POMs; the restacking phenomenon of MXene materials; and the single porous structure prepared by the traditional porous structure preparation method, with relatively low specific surface area and porosity; and the complex preparation process of MXene, POM or POM / MXene-based three-dimensional structures, high cost and great harm to the environment.
[0004] The present invention utilizes POM to grow in situ between MXene layers to increase the MXene interlayer spacing and prevent POMs from dissolving, and then uses a surfactant, dioctadecyldimethylammonium bromide (DODA), to coat POM / MXene through a simple self-assembly process to prepare a POM / MXene-based composite, thereby further inhibiting the dissolution of POM and the stacking of MXene sheets. The composite is dissolved in an organic solvent at a certain concentration and used as a casting liquid. A conductive substrate is used as a current collector and casting is performed under a suitable humidity environment. A POM / MXene-based rime-like porous structure is prepared by the self-assembly process of water droplets, and an electrode with a three-dimensional structure of POM / MXene loaded on a conductive substrate is obtained, which can be used as an electrode material for a supercapacitor. To achieve the above object, the present invention provides the following scheme: The present invention provides an electrode material based on a POM / MXene porous membrane, comprising a conductive substrate and a POM / MXene porous membrane attached thereto, wherein the porous membrane has micrometer-sized dendritic hole channels and micrometer-sized circular holes, the dendritic hole channel size is about 1 to 20 μm, the circular hole average pore size is about 0.1 to 3 μm, the size is relatively uniform, presenting a mesh-like structure, uniformly growing and linking on the POM / MXene dendritic structure to form a rime-like porous structure. The electrode material shows high specific capacitance and long cycle stability, and can be used for the construction of supercapacitors, and the obtained supercapacitors have good specific capacitance, cycle stability and energy density.
[0005] The present invention also provides a method for preparing an electrode material based on a POM / MXene porous membrane, comprising the following steps:
[0006] (1) Mix 0.1-10.0 g FeCl3·6H2O and 0.1-20.0 g H 24 Mo7N6O 24 ·4H2O solid powder is dissolved in 100-3000mL deionized water and stirred to form a uniform suspension, which is the POM precursor liquid.
[0007] (2) dispersing MXene powder in deionized water to prepare a MXene aqueous solution with a concentration of 0.1 to 6.0 mg / mL, and dissolving dioctadecyl dimethyl ammonium bromide (DODA) in an organic solvent to prepare an organic solution with a concentration of 0.1 to 15.0 mg / mL;
[0008] (3) Mixing a certain volume of the POM precursor solution prepared in step (1) with a certain volume of the MXene aqueous solution prepared in step (2), aging at room temperature for more than 24 hours to form a POM / MXene composite aqueous solution; and drying the aqueous solution to form a black solid powder.
[0009] (4) dissolving the POM / MXene powder prepared in step (3) in deionized water to form an aqueous solution, and mixing it with the DODA organic solution prepared in step (2) at a certain concentration ratio, stirring for more than 5 hours, to obtain a POM / MXene-based composite organic solution;
[0010] (5) pouring the organic solution prepared in step (4) on a conductive substrate under high humidity to prepare a POM / MXene-based porous membrane supported on the conductive substrate, i.e., an electrode material based on the POM / MXene porous membrane.
[0011] As a further preferred embodiment of the present invention, the organic solvent in step (2) is chloroform, acetone, toluene, etc.
[0012] As a further preferred embodiment of the present invention, the concentration of the POM precursor solution in step (3) is 1 to 300 mg / mL, the volume of the POM precursor solution is 5 to 300 μL, and the volume of the MXene aqueous solution is 1 to 20 mL, and the two are mixed at a solute mass ratio of 3:1 to 1:6.
[0013] As a further preference of the present invention, in step (4), the concentration ratio of the POM / MXene-based complex aqueous solution and the DODA organic solution is 1:1 to 1:6; the concentration of the POM / MXene aqueous solution is 1.0 to 6.0 mg / mL; and the concentration of the POM / MXene-based complex is 1.0 to 8.0 mg / mL.
[0014] As a further preferred embodiment of the present invention, the humidity in step (5) is 65% to 98%, and the conductive substrate can be carbon cloth, nickel foam, conductive PET, etc.
[0015] Application of an electrode material based on POM / MXene porous membrane in supercapacitors.
[0016] The present invention discloses the following technical effects:
[0017] The present invention discloses an electrode material based on a POM / MXene-based porous membrane, the electrode material includes a conductive substrate and a POM / MXene-based porous membrane loaded thereon, the present invention utilizes POM to grow between MXene layers to improve the self-stacking of MXene and the easy water solubility of POM, and then uses an amphiphilic substance DODA to coat POM / MXene, further suppressing the above problems, preparing a composite soluble in an organic solvent, dissolving a certain amount of the composite in an organic solvent at a suitable concentration to prepare a casting liquid, casting a certain amount of the casting liquid on a conductive substrate under high humidity conditions, and preparing a POM / MXene-based porous membrane through a self-assembly process. The porous membrane structure has micron-scale dendritic hole channels and micron-scale circular holes, the dendritic hole channel size is about 1 to 20 μm, the circular hole average pore size is about 0.1 to 3 μm, the size is relatively uniform, presenting a mesh-like structure, uniformly growing and linking on the POM / MXene dendritic structure, forming a rime-like porous structure. Compared with the three-dimensional holes made by the traditional porous structure preparation method, the introduction of the porous structure can provide more ion active sites and greatly increase the electrolyte storage space, thereby improving the electrochemical performance of the electrode material. At the same time, the rime-like porous structure also reduces the resistance of the material and increases the ion conduction rate on the surface of the material. The preparation method is simple to implement, low in cost, and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 These are scanning electron microscope images of the POM / MXene-based porous structure prepared in Example 1 at different magnifications.
[0019] Figure 2 CV and GCD results of the POM / MXene-based porous and flat membrane structures prepared in Example 1.
[0020] Figure 3 These are the EIS results of the POM / MXene-based porous and flat membrane structures prepared in Example 1.
[0021] Figure 4 This is the cycle stability data of the electrode material based on the POM / MXene porous structure prepared in Example 1 after 7000 cycles at 5 A / g. DETAILED DESCRIPTION
[0022] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0023] Example 1
[0024] (1) Mix 1.1 g FeCl3·6H2O and 5.6 g H 24 Mo7N6O24 ·4H2O solid powder was dissolved in 400mL deionized water and stirred to form a uniform suspension, which was the POM precursor liquid.
[0025] (2) 10 mg of MXene powder was dispersed in 5 mL of deionized water to prepare a MXene aqueous solution with a concentration of 2 mg / mL, and 40 mg of dioctadecyldimethylammonium bromide (DODA) was dissolved in 5 mL of chloroform to prepare an organic solution with a concentration of 8 mg / mL.
[0026] (3) 50 μL of the POM precursor solution prepared in step (1) was mixed with 5 mL of the MXene aqueous solution prepared in step (2) at a solute mass ratio of 1:2, and aged at room temperature for more than 24 h to form a POM / MXene complex aqueous solution; the aqueous solution was dried to form a black solid powder.
[0027] (4) dissolving 10 mg of the POM / MXene powder prepared in step (3) in 5 mL of deionized water and mixing with 8 mg / mL of DODA organic solution, stirring for 5 h, to prepare a POM / MXene-based composite organic solution;
[0028] (5) The organic solution prepared in step (4) is poured on a conductive substrate at 80% humidity to prepare a POM / MXene-based porous membrane supported on the conductive substrate, i.e., an electrode material based on the POM / MXene porous membrane.
[0029] Figure 1 This is a scanning electron microscope image of the POM / MXene porous structure prepared in this example. Figure 1 It can be seen that the size of the dendritic channels in the porous structure is about 10 μm, the circular holes are arranged in a relatively orderly manner, and the average pore size is about 1.8 μm. The porosity is calculated to be 95%.
[0030] Figure 2 The CV graph at 5 mV / s and the GCD graph at 0.3 A / g of the electrode material based on the POM / MXene porous structure prepared in this example are shown in FIG. Figure 2 It can be seen that by introducing the porous structure, the specific capacitance of the electrode material increases from 67.5 F / g of the flat membrane to 128.6 F / g of the porous membrane.
[0031] Figure 3 The EIS results of the electrode material based on the POM / MXene porous structure prepared in this example in the frequency range of 0.01 Hz to 100 kHz are shown in FIG. Figure 3 It can be seen that the introduction of the porous structure significantly reduces the resistance of the electrode material and increases the charge transfer rate.
[0032] Figure 4 The cycle stability data of the electrode material based on the POM / MXene porous structure prepared in this example after 7000 cycles at 5A / g are shown in FIG. Figure 4 It can be seen that the electrode material still maintains 92% of the initial specific capacitance after 7000 cycles at 5 A / g, showing excellent cycle stability.
[0033] This POM / MXene porous structure-based electrode material was used to construct a symmetric supercapacitor, achieving a specific capacitance of 115 F / g, an initial capacitance retention rate of 75% after 5000 cycles at 10 A / g, and an energy density of 20.41 Wh / kg at a power density of 100 W / kg.
[0034] Example 2
[0035] The same as Example 1, other substances and conditions remain unchanged, the difference is that 100 μL of POM precursor solution and 5 mL of MXene aqueous solution are mixed with a solute mass ratio of 1:1, and the above steps are repeated to prepare an electrode material based on a POM / MXene porous structure. The electrode material prepared in this embodiment has a dendritic channel size of 8 μm, a circular hole diameter of 1.5 μm, a specific capacitance of 103.2 F / g, and an initial capacitance retention rate of 86%. After being assembled into a supercapacitor, the specific capacitance is 100 F / g, the initial capacitance retention rate is 71% after 5000 cycles at 10 A / g, and the energy density is 18.75 Wh / kg at a power density of 100 W / kg.
[0036] Example 3
[0037] The same as Example 1, other substances and conditions remain unchanged, the difference is that 33 μL of POM precursor solution and 5 mL of MXene aqueous solution are mixed with a solute mass ratio of 1:3, and the above steps are repeated to prepare an electrode material based on a POM / MXene porous structure. The electrode material prepared in this embodiment has a dendritic channel size of 7 μm, a circular hole diameter of 1.3 μm, a specific capacitance of 82.93 F / g, and an initial capacitance retention rate of 81%. After being assembled into a supercapacitor, the specific capacitance is 75 F / g, the initial capacitance retention rate is 66% after 5000 cycles at 10 A / g, and the energy density is 15 Wh / kg at a power density of 100 W / kg.
[0038] Example 4
[0039] The same as Example 1, other substances and conditions remain unchanged, the difference is that 200 μL of POM precursor solution and 5 mL of MXene aqueous solution are mixed with a solute mass ratio of 2:1, and the above steps are repeated to prepare an electrode material based on a POM / MXene porous structure. The electrode material prepared in this embodiment has a dendritic channel size of 6 μm, a circular hole diameter of 1.4 μm, a specific capacitance of 79.5 F / g, and an initial capacitance retention rate of 80%. After being assembled into a supercapacitor, the specific capacitance is 70 F / g, the initial capacitance retention rate is 65% after 5000 cycles at 10 A / g, and the energy density is 10 Wh / kg at a power density of 100 W / kg.
[0040] Example 5
[0041] The same as Example 1, other substances and conditions remain unchanged, the difference is that the concentration of the POM precursor liquid is 50 mg / mL, 50 μL of the POM precursor liquid is mixed with 5 mL of the MXene aqueous solution, and the above steps are repeated to prepare an electrode material based on a POM / MXene porous structure. The electrode material prepared in this embodiment has a dendritic channel size of 8 μm, a circular hole diameter of 1.7 μm, a specific capacitance of 115 F / g, and an initial capacitance retention rate of 89%. After being assembled into a supercapacitor, the specific capacitance is 102.5 F / g, the initial capacitance retention rate is 71% after 5000 cycles at 10 A / g, and the energy density is 19.75 Wh / kg at a power density of 100 W / kg.
[0042] Example 6
[0043] The same as Example 1, other substances and conditions remain unchanged, the difference is that the concentration of the POM precursor liquid is 200 mg / mL, 50 μL of the POM precursor liquid is mixed with 5 mL of the MXene aqueous solution, and the above steps are repeated to prepare an electrode material based on a POM / MXene porous structure. The electrode material prepared in this embodiment has a dendritic channel size of 8 μm, a circular hole diameter of 1.5 μm, a specific capacitance of 103 F / g, and an initial capacitance retention rate of 86%. After being assembled into a supercapacitor, the specific capacitance is 100 F / g, the initial capacitance retention rate is 71% after 5000 cycles at 10 A / g, and the energy density is 18.5 Wh / kg at a power density of 100 W / kg.
[0044] Example 7
[0045] The same as Example 1, other substances and conditions remain unchanged, the difference is that the concentration of the DODA organic solution is changed to 12 mg / mL, the above steps are repeated to prepare an electrode material based on a POM / MXene porous structure. The electrode material prepared in this embodiment has a dendritic channel size of 10 μm, a circular hole diameter of 2.0 μm, a specific capacitance of 117 F / g, an initial capacitance retention rate of 90%, and after being assembled into a supercapacitor, the specific capacitance is 104 F / g, the initial capacitance retention rate is 73% after 5000 cycles at 10 A / g, and the energy density is 20.2 Wh / kg at a power density of 100 W / kg.
[0046] Example 8
[0047] The same as Example 1, other substances and conditions remain unchanged, the difference is that the concentration of the DODA organic solution is changed to 4 mg / mL, the above steps are repeated to prepare an electrode material based on a POM / MXene porous structure. The electrode material prepared in this embodiment has a dendritic channel size of 10 μm, a circular hole diameter of 1.4 μm, a specific capacitance of 90 F / g, and an initial capacitance retention rate of 82%. After being assembled into a supercapacitor, the specific capacitance is 85 F / g, the initial capacitance retention rate is 73% after 5000 cycles at 10 A / g, and the energy density is 17.5 Wh / kg at a power density of 100 W / kg.
[0048] Example 9
[0049] The same as Example 1, other materials and conditions remain unchanged, the difference is that the conductive substrate is nickel foam, and the above steps are repeated to prepare an electrode material based on a POM / MXene porous structure. The electrode material prepared in this embodiment has a dendritic channel size of 9 μm, a circular hole diameter of 1.5 μm, a specific capacitance of 120 F / g, an initial capacitance retention rate of 91%, and after being assembled into a supercapacitor, the specific capacitance is 114 F / g, the initial capacitance retention rate is 74% after 5000 cycles at 10 A / g, and the energy density is 20.1 Wh / kg at a power density of 100 W / kg.
[0050] Example 10
[0051] The same as Example 1, other materials and conditions remain unchanged, the difference is that the conductive substrate is conductive PET, and the above steps are repeated to prepare an electrode material based on a POM / MXene porous structure. The electrode material prepared in this embodiment has a dendritic channel size of 10 μm, a circular hole diameter of 1.5 μm, a specific capacitance of 80 F / g, an initial capacitance retention rate of 92%, and after being assembled into a supercapacitor, the specific capacitance is 70 F / g, the initial capacitance retention rate is 74% after 5000 cycles at 10 A / g, and the energy density is 14 Wh / kg at a power density of 100 W / kg.
[0052] Comparative Example 1
[0053] The same as Example 1, other materials and conditions remain unchanged, the only difference is that there is only MXene composite in the casting liquid, no POM, repeat the above steps to prepare an electrode material based on MXene porous structure. The electrode material prepared in this comparative example has a small specific capacitance and poor cycle stability.
[0054] Comparative Example 2
[0055] The same as Example 1, other materials and conditions remain unchanged, the only difference is that there is only POM composite in the casting liquid, no MXene composite, repeat the above steps to prepare an electrode material based on a POM porous structure. The electrode material prepared in this comparative example has a small specific capacitance and poor cycle stability.
[0056] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. An electrode material based on POM / MXene porous membrane, characterized in that: The invention comprises a conductive substrate and a POM / MXene porous membrane attached thereto.
2. The electrode material based on POM / MXene porous membrane according to claim 1, characterized in that: There are micron-scale branch-like pore channels and circular pores in the POM / MXene porous membrane. The size of the branch-like pore channels is about 1 to 20 μm, and the average pore size of the circular pores is about 0.1 to 3 μm. They are relatively uniform in size, presenting a mesh-like structure, which grows uniformly and links on the POM / MXene branch-like structure to form a rime-like porous structure.
3. A method for preparing an electrode material based on a POM / MXene porous membrane according to claim 1 or 2, characterized in that: The steps include: (1) Mix 0.1-10.0 g FeCl3·6H2O and 0.1-20.0 g H 24 Mo7N6O 24 ·4H2O solid powder is dissolved in 100-3000mL deionized water and stirred to form a uniform suspension, which is the POM precursor liquid. (2) dispersing MXene powder in deionized water to prepare a MXene aqueous solution with a concentration of 0.1 to 6.0 mg / mL, and dissolving dioctadecyl dimethyl ammonium bromide (DODA) in an organic solvent to prepare an organic solution with a concentration of 0.1 to 15.0 mg / mL; (3) Mixing a certain volume of the POM precursor solution prepared in step (1) with a certain volume of the MXene aqueous solution prepared in step (2), aging at room temperature for more than 24 hours to form a POM / MXene composite aqueous solution; and drying the aqueous solution to form a black solid powder. (4) dissolving the POM / MXene powder prepared in step (3) in deionized water to form an aqueous solution, and mixing it with the DODA organic solution prepared in step (2) at a certain concentration ratio, stirring for more than 5 hours, to obtain a POM / MXene-based composite organic solution; (5) The organic solution prepared in step (4) is poured on a conductive substrate under high humidity to prepare a POM / MXene-based porous membrane supported on the conductive substrate, i.e., an electrode material based on the POM / MXene porous membrane.
4. The method for preparing an electrode material based on a POM / MXene porous membrane according to claim 3, characterized in that: The organic solvent in step (2) is chloroform, acetone, toluene, etc.
5. The method for preparing an electrode material based on a POM / MXene porous membrane according to claim 3, characterized in that: In step (3), the concentration of the POM precursor solution is 1 to 300 mg / mL, the volume of the POM precursor solution is 5 to 300 μL, and the volume of the MXene aqueous solution is 1 to 20 mL. The two are mixed at a solute mass ratio of 3:1 to 1:
6.
6. The method for preparing an electrode material based on a POM / MXene porous membrane according to claim 3, characterized in that: In step (4), the concentration ratio of the POM / MXene-based complex aqueous solution and the DODA organic solution is 1:1 to 1:6; the concentration of the POM / MXene aqueous solution is 1.0 to 6.0 mg / mL; and the concentration of the POM / MXene-based complex is 1.0 to 8.0 mg / mL.
7. The method for preparing an electrode material based on a POM / MXene porous membrane according to claim 3, characterized in that: In step (5), the humidity is 65% to 98%, and the conductive substrate can be carbon cloth, nickel foam, conductive PET, etc.
8. Use of the electrode material according to claim 1 or 2 in a supercapacitor.